THE DYNAMICS OF IMPLEMENTING INTERNATIONAL NORMS ON THE ELIMINATION OF SEXUAL VIOLENCE IN INDONESIA - Yunazwardi, Muhammad Iqbal; Ikawati, Erina (UI Scholars Hub, 2025)
This study analyses the dynamics of the implementation of international norms regarding the elimination of sexual violence in Indonesia, with a focus on the influence of narrative contestation on the protection of victims. Although Indonesia has ratified the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW), implementing these norms at the domestic level still faces various challenges. The ratification of the Sexual Violence Crime Law (TPKS Law) marks a significant milestone in the protection of victims. Still, its effectiveness is doubtful due to resistance from domestic actors and political interests that shape the public will. Through a norm diffusion approach and qualitative analysis, this study explores how norm drivers play a role in promoting and internalising the norm of eliminating sexual violence in Indonesia. The analysis results indicate that domestic social and political resistance hinders the acceptance of these norms, thereby limiting the state's commitment to protecting victims. This study highlights the importance of more adaptive strategies from the state and normative actors in overcoming domestic obstacles to implementing global human rights norms.